KOLASE BAHAN ALAM - Siti Nurkhasanah (Jurnal Abadimas Adi Buana, 2017)
The implementation of KKN PPM is implemented, such as training activities collage of natural materials in kindergarten Aisyiyah Bustanul Atfal, the trainees are students-students with a number of 31 children. the location of the training activities carried out at the Village Hall Dermo, District Benjeng, Gresik. Selection of the type of skill is partly due to the activities collage of natural materials still little known to the child, even many of the students lack of interest dents collage collage mainly natural materials, and a lack of impetus from educational institutions and parents so as to enable the development of activities of collage of natural materials in order to can create learning activities that are creative and innovative. The implementation of the PPM service learning activities are more focused on aspects of practice rather than theory, with a ratio of 80% practical and 20% theory, so students can further dents to imagine in following the activities collage of natural materials and provide new experiences with activities directly with media provided. keywords: collage, material, natural